Tactics of therapy for acute gastrointestinal bleeding - Pliuta, Iryna (The Ukrainian Scientific Medical Youth Journal, 2022)
The number of patients with non-varicose acute gastrointestinal bleeding who need anticoagulants has increased in the last decade. The choice of method and amount of safe therapy in case of acute gastrointestinal bleeding is complicated. A reasonable optimal balance of therapy between hypo- and hypercoagulant components was determined on the basis of an objective assessment of risk factors for re-bleeding and thromboembolic complications. A council of surgeons, resuscitators and cardiologists decided on the rationality of anticoagulant therapy and its scope. With a low risk of recurrent bleeding and a high risk of thromboembolic complications, hemostatic therapy (tranexamic acid, ethamsylate) was combined with the introduction of low molecular weight heparin (bemiparin) in prophylactic doses. An important parameter for the appointment of conservative therapy were thromboelastography. The data obtained indicate the safety of hemostatic and thromboprophylactic therapy (the level of re-bleeding did not differ from the level of bleeding without the use of low molecular weight heparins, according to the literature). Stroke was observed in only 1 patient. The complexity, multifactorial and diversity of clinical conditions of patients with acute gastrointestinal bleeding indicates the need for further study of the treatment problem.